PENGEMBANGAN FASILITAS KURSI BELAJAR YANG ERGONOMIS DAN ANTROPOMETRI UNTUK ANAK HIPERAKTIF DI SEKOLAH INKLUSI - Laswandi, Hartini; Mularsih (Almrh), Heni (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
There are complaints of discomfort and difficulty in dealing with the activeness of hyperactive students felt in inclusive elementary schools. Anxious attitude when sitting, always disturbing friends while learning is taking place, this can interfere with the learning process, both for other normal students and hyperactive students. The purpose of this research is to develop a special study chair design for hyperactive students that is ergonomic based on anthropometry. The method used in this research is an ergonomic approach to the anthropometric method and the design method that prioritizes quality. Develop ergonomic and anthropometric chair products based on devine, design and develop procedures. This approach is used to determine the dimensions of the chair design. Study chair facilities that are ergonomic and anthropometric in learning need to be developed in every school, both public and inclusive schools. Guidelines for the design of activities and facilities for hyperactive students during learning activities, based on the analysis of activities and facilities for hyperactive students in inclusive schools. The design result of the development of a special study chair for hyperactive students is a chair design with adjustable armrests, flexible chairs and footrests with a slider system that can answer user complaints. Chair design with armrests, flexible and strong footrests can provide comfort for hyperactive students and reduce their activity. Inclusion schools are expected to facilitate learning facilities, especially for students with special needs. Adanya keluhan ketidaknyamanan dan kesulitan dalam menghadapi keaktifan siswa hiperaktif dirasakan di sekolah dasar inklusi. Sikap cemas saat duduk, selalu mengganggu teman saat belajar berlangsung hal ini dapat mengganggu proses belajar, baik untuk siswa normal lainnya maupun siswa hiperaktif. Tujuan dari penelitian ini adalah untuk mengembangkan desain kursi belajar khusus untuk siswa hiperaktif yang ergonomis berdasarkan antropometri. Metode yang digunakan dalam penelitian adalah pendekatan ergonomi terhadap metode antropometri dan metode desain yang mengutamakan kualitas. Mengembangkan produk kursi yang ergonomis dan antropometris berdasarkan dengan prosedur devine, design, dan develop. Pendekatan ini digunakan untuk menentukan dimensi desain kursi. Fasilitas kursi belajar yang ergonomi dan antropometri dalam pembelajaran perlu dikembangkan di setiap sekolah, baik sekolah umum maupun sekolah inklusi Pedoman desain aktivitas dan fasilitas siswa hiperaktif saat kegiatan belajar, berdasarkan analisis aktivitas dan fasilitas siswa hiperaktif di sekolah inklusi. Hasil desain dari pengembangan kursi belajar khusus untuk siswa hiperaktif adalah desain kursi dengan sandaran tangan yang bisa disetel, kursi yang fleksibel dan sandaran kaki dengan sistem slider dapat menjawab keluhan pengguna. Desain kursi dengan sandaran tangan, pijakan kaki yang lentur dan kuat dapat memberikan kenyamanan bagi siswa hiperaktif dan mengurangi keaktifannya. Sekolah inklusi diharapkan untuk memfasilitasi sarana belajar terutama bagi siswa berkebutuhan khusus ini.